A hidden menace: Cardiovascular disease in South Africa and the costs of an inadequate policy response - Maredza, Mandy; Hofman, Karen J.; Tollman, Stephen M. (SA Heart Journal, 2017)
The cardiovascular disease (CVD) burden in South Africa (SA) is increasing amongst all age groups and is predicted to become the prime contributor to overall morbidity and mortality in the over 50-year age group. Several factors contribute to this – an epidemiological transition, which has seen a rise in chronic non-communicable disease, and a demographic transition with much reduced fertility and a growing proportion of the population above 60 years. In parallel with unfolding urbanisation, the population burden of vascular risk factors namely hypertension, hypercholesterolemia, diabetes and obesity has increased. The scale of CVD burden poses a threat to the health system and calls for timely intervention. This paper discusses the burden of CVD in SA and current initiatives to address it. Evidence is presented from studies that focus on prevention including salt reduction and trans-fatty acids legislation. The economic and clinical impact of an inadequate private and public sector response is summarised. The paper documents lessons from other countries and proposes health systems strengthening measures that could improve care of patients with CVD.